A Critical Review on the Book Fundamentals and Principles of Islamic Sociology - Moslem Taheri Kalkoshvandi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this article, we will critically review the book Fundamentals and Principles of Islamic Sociology written by Dr. Farid Younes and translated by Gholamreza Jamshidiha and Ganjababi. In order to accelerate the process aimed at achieving the desired model of "Islamic sociology", it is necessary to present the achievements and fundamental actions of Muslim thinkers that have been produced in this field and to conduct a continuous critical evaluation of them. The sum of these conversations should be removed. Effective steps to achieve a clear mentality towards the field of "Islamic social sciences". The research method in this article will be the qualitative method of content analysis, in that after introducing the bibliographic information, the author, translator and expressed the methodology of the present critique, in order to achieve a clear description of the book. The analysis will be achieved through analysis and interpretation of the content of the book by emphasizing the content and structural aspects of the book. An analysis that focuses on the author's historical, sociological, and religious findings. In this article, we try to help the review of the present book by combining descriptive skills and critical analysis.